Pengaruh Punishment, Reward, dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. PG Rajawali 1 - Rendy Satrio Wicaksono; Pardiman Pardiman; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2023)
Abtract The purpose of this study was to determine the effect of punishment, reward and work motivation on employee performance at PT. PG Rajawali 1. This research is a quantitative research with technical data collection using a questionnaire. The sample in this study amounted to 72 respondents. Place This research was conducted at PT. PG Rajawali 1 Jl. Raya Krebet No. 10 districts. Bululawang, Kab. Malang, East Java. The sampling technique used is the accidental sampling method. Processing of primary data using analysis of Statistical Package for Social Science (SPSS) version 25. technique with multiple regression analysis method. The results of this study indicate that partially each of the independent variables has a positive and significant effect on employee performance, and together they have a simultaneous effect on employee performance. Keywords : punishment, reward, work motivation, and employee performance